Using the gravity equation to explain the portuguese immigration-trade link - Faustino, Horácio C. (2008)
This paper tests the relation between immigration and Portuguese bilateral trade. Using a panel data analysis, the results show that the stock of immigrants has a positive effect on Portuguese exports, imports and bilateral intra-industry trade. The underlying assumption is that immigration contributes to decrease the costs of transactions, which in turn promotes trade flows. The results do not confirm the hypothesis of a negative effect of immigration on Portuguese exports. Our findings suggest that when immigrants to Portugal come from a Latin partner-country, the effects on trade are stronger than in the case of immigrants from non-Latin countries. The study is based on an extended gravitational model, in order to incorporate the qualitative factors as control variables.